UNSUR MANAJEMEN DALAM PENGELOLAAN LEMBAGA PENDIDIKAN ISLAM DI INDONESIA - FAJRI DWIYAMA (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2018)
Abstract: Islamic education institutions in Indonesia face two challenges, namely; internal and external. Internally, Islamic education is faced with the classic problem of the low quality of human resources in education management. The causes include poor quality and education staff development and selectivity of education personnel. Furthermore externally, Islamic education institutions faced three major issues; globalization, democratization, and liberalization. The issue of globalization that is identical with market orientation and mechanism also affects the world of education. That way in education also includes awareness about how to attract and convince the community of the type and model of education. From here, the education world is ready or not ready to be involved in competition to gain public trust. To face these challenges Islamic Education institutions must maximally manage and empower all elements of management in the management of educational institutions. A good understanding of the elements of management can have an impact on the readiness of educational institutions to manage their institutions well in any condition to be the best and foremost. Keywords: Elements of Management, Management, Education, Islam